The impact of acetabular labral tears on sexual activity in women. Issue 4 (31st December 2019) - Raut, Shruti; Kamal, Jessica; Norrish, Alan; Khanduja, Vikas
Abstract: A healthy sex-life is an important component of a good quality of life. However, sexual function may be inhibited in women with acetabular labral tears because of the labrum being caught between the femoral head neck junction and the acetabular rim during flexion and/or abduction of the hip. The aim of this article is to quantify the effect that acetabular labral tears may have on the sexual lives of women and to establish the extent to which they may be expected to resolve after arthroscopic intervention. The article also highlights the importance of including questions related to the impact on sexual activity as a routine part of our taking history for a young adult with hip pain, to gain a true appreciation of the impact the symptoms have on the day-to-day lives of our patients.